Analysis of Personal Hygiene of the Food Handlers, Basic Sanitation and Density of Flies in Restaurants Around the Market Center of Kabanjahe Year 2017 - Bangun, Henny Arwina; Sinaga, Lia Rosa Veronika; Ginting, Hestina; Baster, I Cokna (Sari Mutiara Indonesia University Press, 2018)
Abstract Hygiene is a health effort by maintaining and protecting the cleanliness of individual subjects, while sanitation is a health effort by maintaining and protecting the cleanliness of the environment of the subject.The purpose of sanitation and hygiene efforts is to prevent the onset of diseases and poisoning and other health problems as a result of the interaction of human environmental factors, which are spread through flies as a mechanical vector of disease transmission.There are 4 impacts of not implementing personal hygiene and sanitation on food, namely 1) Contamination, both directly and cross-linked, 2) Poisoning, 3) Decay, and 4) Counterfeiting. This study aims to find out how personal hygiene of food handlers, basic sanitation and density of flies in restaurants around the market center of Kabanjahe.The type of the present study is descriptive by using a quantitative research method.The study was conducted in May-June 2017. The sample in this study consisted of 21 restaurants. Data is obtained by conducting in-depth interviews using interview guidelines. The results showed that there were 19 (90,5%) restaurants in the category of quality C, 2 (9.5%) restaurants in the category of quality B, while there were no restaurants in category of quality A. High density of flies is found in as many as 21 restaurants (100%). Whereas the density of flies classified as low and medium was not found in this study. It is recommended that the restaurant manager should be more aware of the importance of maintaining personal hygiene of food handlers so that every food and drink served is really clean and healthy.And for the restaurant owner to pay attention to the distance between the trash can and the location of the food presentation, and coordinate with the garbage transport officer of the Sanitation Department to transport garbage every day